Housing estates in Europe. Poverty, ethnic segregation and policy challenges. - (:unkn) unknown (Springer Open, 2018)
The book explores the formation and socio-spatial trajectories of large housing estates in Europe. Are these estates clustered or scattered? Which social groups originally had access to residential space in housing estates? What is the size, scale and geography of housing estates, their architectural and built environment composition, services and neighbourhood amenities, and metropolitan connectivity? How do housing estates contribute to the urban mosaic of neighborhoods by ethnic and socio-economic status? What types of policies and planning initiatives have been implemented in order to prevent the social downgrading of housing estates? The collection of chapters addresses these questions from a new perspective previously unexplored in scholarly literature. The social aspects of housing estates are thoroughly investigated (including socio-demographic and economic characteristics of current and past inhabitants; ethnicity and segregation patterns; population dynamics; etc.), and the physical composition of housing estates is described in significant detail (including building materials; building form; architectural and landscape design; built environment characteristics; etc.). The book is timely because the recent global economic crisis and Europe's immigration crisis demand a thorough investigation of the role large housing estates play in poverty and ethnic concentration. Through case studies of housing estates in 14 European centers, the book also identifies policy measures that have been used to address challenges in housing estates throughout Europe.
Keywords: Wohnungswesen; Wohnungspolitik; Wohnsiedlung; Siedlung; Bewohner; Arbeitersiedlung; Sozialer Wohnungsbau; Segregation; Armut; Stadtsoziologie; Sozialgeographie; Großsiedlung; Bestand; Erneuerung; Kommunaler Wohnungsbau; Wohnsoziologie